Circulating tumor DNA use in a community oncology practice - Chamberlain, Erin D.; Costantini, Carrie L.; Xavier, Marin F. (Translational Cancer Research, 2019)
Background: This retrospective single center study aimed to describe circulating tumor DNA (ctDNA) comprehensive genomic profiling (CGP) utilization in a community practice for patients with advanced solid tumors. Methods: All patients were included who were seen at the Scripps Hillcrest Oncology Clinic (San Diego, CA, USA) between September 2016 to March 2018 who had ctDNA assay testing performed. In this cohort, all ctDNA testing was performed to aid therapeutic decision making with wide variety in both the type of advanced solid tumor, as well as the line of therapy. Results: Of the assays performed in the 41 patients included in this review, 42% of therapeutic actions following ctDNA assay results were influenced by the ctDNA result, including initiation of the corresponding Federal Drug Administration (FDA) approved therapy, placement on clinical trial, and initiation of off label-targeted options. In addition, CGP results guided clinicians away from futile or harmful treatments, such as EGFR inhibition in colorectal cancer patients with discovered KRAS mutations. No additional prognostic or therapeutic information was gathered in one quarter of patients for which ctDNA was drawn. Furthermore, discovered genomic alterations by ctDNA testing did not influence therapeutic action in 58% of cases. Conclusions: These results highlight the conundrum that having additional information regarding an individual’s tumor biology does not yet translate into meaningful targeted therapy in the majority of cases. Further studies are needed regarding ctDNA utilization to help guide community oncologists who will continue to face the choice between targeted therapy, immunotherapy, and cytotoxic chemotherapy as science advances.